2012
DOI: 10.1542/peds.2011-2067
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive Status Epilepticus: The Encephalopathic Pediatric Patient

Abstract: A high prevalence of NCSE was observed, comparable to adult studies, but within a wider range of inpatient settings. Children with acute encephalopathy should undergo continuous EEG. This evaluation is more urgent if certain clinical risk factors are present. Optimal duration of monitoring and the effect of NCSE on prognosis should be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
109
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 38 publications
18
109
1
Order By: Relevance
“…15,27 A number of single-center studies have demonstrated an association between electrographic seizures or electrographic status epilepticus and worse outcome in critically ill children. 11,12,14,16,17,28 Our data also indicate that electrographic status epilepticus was associated with higher mortality, even after adjusting for the neurologic diagnosis category and initial EEG background category. However, the current data cannot establish whether electrographic status epilepticus is a modifiable risk factor for mortality or is a nonmodifiable biomarker of severe brain injury leading to mortality.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…15,27 A number of single-center studies have demonstrated an association between electrographic seizures or electrographic status epilepticus and worse outcome in critically ill children. 11,12,14,16,17,28 Our data also indicate that electrographic status epilepticus was associated with higher mortality, even after adjusting for the neurologic diagnosis category and initial EEG background category. However, the current data cannot establish whether electrographic status epilepticus is a modifiable risk factor for mortality or is a nonmodifiable biomarker of severe brain injury leading to mortality.…”
supporting
confidence: 61%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The majority of electrographic seizures were not accompanied by any clinical signs, 1,3,8,[10][11][12][13][14] even in nonparalyzed patients. 1,14 Therefore, accurate seizure identification requires CEEG.…”
mentioning
confidence: 89%
See 3 more Smart Citations